Implementing Wattpad-Based Pentigraph Writing in Indonesian Language Education: An Empirical Evidence - Setiawan, Kodrat Eko Putro; Juwari, Juwari; Kasimbara, Devi Cintia (Journal of Language and Literature Studies, 2025)
This study aims to describe the implementation of pentigraph writing instruction using the Wattpad platform. The method employed is qualitative with a case study approach. The data sources include images, words, phrases, and Wattpad accounts of students. The data were collected from 28 students in the fourth semester of the Indonesian Language and Literature Education program during the 2024–2025 academic year (even semester). This research was conducted at PGRI University Madiun (UNIPMA). Data sources in this study were obtained through observation, interviews, and documentation. Data collection techniques in this study included observation, which involves observing a target object and recording its condition; interviews, which are conversations between the informant and the interviewer aimed at obtaining information; and documentation, which involves collecting data from documents. Documentation consists of collecting data from documents. The coding process in this study involved labeling or coding parts of the data derived from the students’ pentigraf works. The results of this study indicate that the strategy of learning to write pentigraf using Wattpad media among students majoring in Indonesian Language and Literature has several benefits, including: students can create independently according to their ideas; encouraging students to think creatively and innovatively in developing a complete story within the limitation of only three paragraphs; training students to develop their creativity by describing their surroundings; increasing interest in reading and writing; enhancing appreciation for digital written works; supporting creative writing learning; and building a virtual creative writing community (pentigraf).